The Influence of Organizational Culture and Work Discipline on Sustainable Employee Performance at the Village Office with Work Motivation as a Mediating Variable in the Kembangan District Area - Adhitya, Rizal; Soehari, Tjiptogoro Dinarjo (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the influence of organizational culture and work discipline on the performance of sustainable employees with work motivation as a mediating variable in the Village Office in Kembangan District. The research method used a quantitative approach with questionnaires to 60 employees, analyzed through SEM-PLS using SmartPLS 4.0. The results of the study show that organizational culture and work discipline have a significant positive effect on work motivation and sustainable employee performance. Work motivation also has a significant effect on employee performance and acts as a partial mediator in the organization's cultural relationship to sustainable employee performance. These findings affirm the importance of strengthening organizational culture, work discipline, and motivation in improving the quality of performance of government apparatus in a sustainable manner.